2024
DOI: 10.1002/acm2.14288
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality assurance of multi‐leaf collimator using the structural similarity index

Hong Zhang,
Baoshe Zhang,
Giovanni Lasio
et al.

Abstract: PurposeThis study aims to evaluate the viability of utilizing the Structural Similarity Index (SSI*) as an innovative imaging metric for quality assurance (QA) of the multi‐leaf collimator (MLC). Additionally, we compared the results obtained through SSI* with those derived from a conventional Gamma index test for three types of Varian machines (Trilogy, Truebeam, and Edge) over a 12‐week period of MLC QA in our clinic.MethodTo assess sensitivity to MLC positioning errors, we designed a 1 cm slit on the refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Intensity-modulated radiation therapy achieves optimal treatment dose distribution by superimposing a series of irregular treatment fields shaped by a multi-leaf collimator (MLC) on the tumor, which generates a steep dose gradient around the tumor. [1][2][3][4][5][6][7][8][9] The dosimetric advantages of intensity-modulated radiotherapy are highly dependent on the positioning accuracy of the MLC. [8][9][10][11][12] Many studies have shown that MLC leaf position errors can lead to incorrect dose delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensity-modulated radiation therapy achieves optimal treatment dose distribution by superimposing a series of irregular treatment fields shaped by a multi-leaf collimator (MLC) on the tumor, which generates a steep dose gradient around the tumor. [1][2][3][4][5][6][7][8][9] The dosimetric advantages of intensity-modulated radiotherapy are highly dependent on the positioning accuracy of the MLC. [8][9][10][11][12] Many studies have shown that MLC leaf position errors can lead to incorrect dose delivery.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The dosimetric advantages of intensity-modulated radiotherapy are highly dependent on the positioning accuracy of the MLC. [8][9][10][11][12] Many studies have shown that MLC leaf position errors can lead to incorrect dose delivery. The dosimetric consequences of leaf position errors would be more pronounced for treatment fields where the distance between opposing leaves is typically small.…”
Section: Introductionmentioning
confidence: 99%